The best 100 free apps for libraries - Hahn, Jim (The Scarecrow Press, Inc., 2013)
In this guide, the author, a librarian, has carefully culled the over 500,000 available apps down to the 100 that are the absolute best for day-in, day-out library services. It covers apps for Apple and Android devices, including tablets. Each entry contains: a basic summary of how each app operates ; at least one example of how that app can be used by a librarian ; one example of how it can help a library user access library services ; a section highlighting critical limitations and apps that may better serve a librarian's needs, and ; the next possible iteration of the app. Entries are accompanied by a photo of the app in action, so this current guide is both descriptive and visual. Introductory and final chapters cover using apps in library settings and library services as well as what the future should bring in this area. This guide is intended as an introduction for those with little or no app experience and for those wanting to know more about app uses for information access.